Hydrogen-assisted suspension roasting for pre-reducing lateritic nickel ore: Comparison with CO reduction - Zhe Bai; Jiahao He; Mingxing Wang; Shaokai Cheng; Shuai Yuan; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Transcription factor TaPIL1-mediated iron accumulation in wheat - Yanjun Meng; Zijia Tian; Jiayi Fan; Zhouxiang He; Bo Yu; Changqing Du; Tiancai Guo; Qiang Ge; Guozhang Kang (Plant Science, 2026)

A dual-functional heterosalt additive enables synergistic interphase-bulk engineering for advanced nickel-rich cathodes - Dongni Zhao; Jing Luo; Zixiang Su; Hongzeng Dou; Jingzuo He; Junwei Zhang; Yanjun Zhao; Xinfang Xu; Peng Wang; Ningshuang Zhang; Xiaoling Cui; Shiyou Li (Chemical Engineering Journal, 2026)

Size-resolved airborne particle control in a dental operatory: field comparison of window opening, portable air purifier, and UV air disinfection - Chen Chen; Di Zhang; Xiaoyi Xiao; Chuanhao Wang; Ruixin Nie; Xiaojing Lin; Mengmeng Cao; Meiqiu Hong; Yanjun Su; Bin Zhao; Shanshan Shi; Mingyao Yao; et al. (Building and Environment, 2026)

Isomucronulatol attenuates liver aging by inhibiting GSK-3β acetylation and promoting β-catenin accumulation - Peiyao Chen; Baolian Wan; Fei Yu; Yanqiu Zhang; Mengmeng He; Enyi Wu; Yanjun He; Hui Zhong; Hao Zhang (Journal of Natural Medicines, 2026)

Morphodynamic adjustments of the Lower Yangtze River during 1988–2023: Integrated effects of sediment reduction and rocky outcrops - Lei Zhang; He Qing Huang; Hui Li; Zhongwu Jin; Chao Guo; Peng Yang; Yanjun Wang; Tianwei Qian (Geomorphology, 2026)

Corrigendum to “Layered Bayesian model comparison and uncertainty quantification for CPTU dissipation test inversion” [Comput. Geotech. 201 (2027) 108489] - Jingtong He; Liangfu Xie; Caijin Wang; Xuejun Liu; Jun Wang; Zhiming Liu; Xianming Hou; Yanjun Li; Tao Zhang; Annan Zhou; Songyu Liu; Guojun Cai (Computers and Geotechnics, 2026)

A near-infrared fluorescent probe lights up protective carbon monoxide during inflammation in live systems - Sihang Lv; Longyang Yang; Changjian Wu; Yangtian Liu; Yanjun He; Yuyao Cao; Pengfu Li; Zhongchang Wang; Hai-Liang Zhu (Analytica Chimica Acta, 2026)

Spectral and structural analysis of a new lactone metabolite isolated from a mangrove endophytic fungus - Meijing Tan; Shichao Ju; Fan He; Wenjun Li; Youquan Wei; Rui Pi; Xishan Huang; Yanjun Zhang (Natural Product Research, 2026)

A few-shot fault diagnosis method for ship motors based on multi-source data and multi-view task guidance - Yuan Xu; Deqiang He; Chunyang Dai; Zhenzhen Jin; Yanjun Chen; Yang Fu (Ocean Engineering, 2026)

Corrigendum to “Integrative phylogenetics and geography unveil Quaternary diversification and mitochondrial-nuclear discordance in Odorrana schmackeri sensu lato (Anura, Ranidae): Roles of Qinghai-Tibetan uplift, climate oscillations, and asymmetric gene flow”. [Mol. Phylogenet. Evol. 216 (2026) 108528] - Yanjun Zhu; Zhuo Chen; Yuxiao He; Xinyue Yang; Xiaofei Zhai; Qiuya Wang; Xiaohong Chen; Xiang Ji (Molecular Phylogenetics and Evolution, 2026)

SEC10 suppresses KLF15-mediated transcriptional activation of JAK1 and promotes BoHV-1 replication - Wenqing Ma; Xiao Yu; Yanan Xu; Fachao Sun; Mengrui Zhao; Xinlei Wang; Yanjun Huan; Xin Yin; Hongmei Wang; Hongbin He (Veterinary Microbiology, 2026)

Fluorometric and colorimetric dual-mode detection of tert-butylhydroquinone in food samples using Mn3O4/AuNPs composite nanozyme and Cu,I-doped carbon dots - Mingzhu Liu; Xueyan He; Bo Peng; Jin Wu; Zunquan Zhao; Jialei Bai; Jingran Sun; Yanjun Fang (Food Chemistry, 2026)

Dauricine ameliorates intestinal inflammation and oxidative stress in DSS-induced colitis through TLR4/NLRP3/GSDMD-mediated pyroptosis and Nrf2 pathway - Lin Wang; Jingyuan Liu; Jiayi Wang; Yuxin Xie; Yanan Gao; Daili Xu; Jing Li; Jing Dong; Bingyao Li; Yanjun Cao; Yang Li; Jiao He (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrative phylogenetics and geography unveil Quaternary diversification and mitochondrial-nuclear discordance in Odorrana schmackeri sensu lato (Anura, Ranidae): Roles of Qinghai-Tibetan uplift, climate oscillations, and asymmetric gene flow - Yanjun Zhu; Zhuo Chen; Yuxiao He; Xinyue Yang; Xiaofei Zhai; Qiuya Wang; Xiaohong Chen; Xiang Ji (Molecular Phylogenetics and Evolution, 2026)

Holocene climate optimum moisture variability in the monsoon marginal zone of northern China revealed by multi-proxy stalagmite records - Shouyi Huang; Yanjun Cai; Gang Xue; Xinhui Zhang; Mei He; Ruoxin Li; Yingying Wei; Le Ma; Xing Cheng; Haiwei Zhang; Hai Cheng (Global and Planetary Change, 2026)

Covalently bonded ZnO-reinforced waterborne polyurethane incorporating carboxymethyl chitosan with synergistic antibacterial and antifouling functions - Yanjun Liu; Shurun Li; Jian Bin Zhen; Henghui Zhang; Ruifei Hao; Wenying Liu; Yayue He; Lina Dong (Chemical Engineering Journal, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

The temperature and multi-species evolution during the oxidation of CH3OH/NH3 blends behind reflected shock waves - Dao Zheng; Youquan Yang; Haoyu Tian; Zhimin Peng; Dong He; Yanjun Ding; Yanjun Du (Fuel, 2026)

Enzyme-detonated CRET nanocascade ignites endogenous chemiluminescence to empower self-sufficient photodynamic therapy and tumor-specific imaging - JiaXin Zhu; YanJun He; XiaoQian Wu; KangDi Teng; YiTeng Long; Yuan Zhang; Hui Sun; WenYuan Liu; Feng Feng; Wei Qu (Chemical Engineering Journal, 2026)

Factors affecting the quality of Cistanche herbal: from the content of bioactive components - Jing He; Yanjun Yue; Jing Zhao; Ruiwen Shi; Xin Jia; Haibin Guan; Ying Zhang (Phytochemistry Reviews, 2026)

Enhanced COP absorption refrigeration using R-1243zf/phosphonium based ILs with compression assistance for low-grade heat - Yanjun Sun; Haiqi Zheng; Bohao Yin; Wenqiang Zhang; Jianjun Meng; Dianbo Xin; Xiaopo Wang; Maogang He (International Journal of Refrigeration, 2025)

Acoustic emission-based damage assessment and failure mechanism analysis on CFST columns with different joint configurations under compression-bending loads - Enchao Rong; Junfu He; Liqiang Tang; Kaizhong Xie; Yanjun Chang (Engineering Structures, 2025)

The Holocene stalagmite trace element and Sr isotope records from Central China and the inferred hydroclimate changes - Yuting Wu; Yanjun Cai; Fugui Xiao; Mei He; Shouyi Huang; Xiangkun Zhai; Ruoxin Li; Gang Xue; Hanying Li; Chunlei Zong; Hai Cheng (Chemical Geology, 2025)

Lactobacillus acidophilus alleviates polysorbate-80-induced colitis through regulating intestinal microbiota and inhibiting indoleamine 2,3-dioxygenase 1 - Haibin Guan; Xinyuan Tian; Menghe Liu; Yanjun Yue; Jing He; Jianxia Gao; Song You (Archives of Microbiology, 2025)

Development and validation of 10 K liquid chip for Inner Mongolia cashmere goat - Qi Xu; Haijiao Xi; Dongmei Shen; Tao Zhang; Jinquan Li; Rui Su; Qi Lv; Yanjun Zhang; Ruijun Wang; Na Wang; Baichuan Liu; Dong He; et al. (Small Ruminant Research, 2025)

In situ probing and microstructural evolution mechanisms of hydrogen-derived manganosite (MnO) during oxidative cooling - Wu Zijian; Yuan Shuai; Zhu Feng; Gao Peng; Li Yanjun; He Jiahao (Minerals Engineering, 2025)

Mechanisms driving spectral properties and their associations with above-ground biomass dynamics in a temperate forest - Pengcheng Jiang; Han He; Zikun Mao; Yanjun Su; Mengxu Zhang; Zhichao Xu; Meihui Zhu; Jin Yin; Hongyi Jiang; Shuai Fang; Xugao Wang (Forest Ecology and Management, 2025)

Molecular fingerprints of dissolved organic matter leached from microplastics over prolonged photochemical aging: Implications for aquatic carbon cycling - Zekun Zhang; Zhao Liang Chen; Yanjun Liu; Yuanbi Yi; Ruanhong Cai; Ming Ye; Mengyang Liu; Meng Yan; Kenneth M.Y. Leung; Ding He (Water Research, 2025)

Spatiotemporal diversification enables sustainable cotton-soybean production with enhanced yield and reduced emissions - Qingqing Lv; Ning He; Baojie Chi; Shizhen Xu; Zhenhuai Li; Li Wang; Yanjun Zhang; Dongmei Zhang; Zhengpeng Cui; Jianlong Dai; Junjun Nie; Yongjiang Zhang; et al. (Journal of Cleaner Production, 2025)

Using an integrated model of the extended theory of planned behavior and the temporal self-regulation theory to explain the sugar-sweetened beverage consumption in college students - Zhiqing Hu; Rui Meng; Tongtong Sheng; Qiran Cao; Yanjun Sun; Jian Yin; Yuan He (Appetite, 2025)

Comparative unravelling the antifungal activity and mechanism of oleuropein and matrine inhibiting the growth of phytopathogen Fusarium spp. - Jiaxin He; Jianmei Dong; Wenwen Zhang; Yaya Cheng; Jiali Xie; Xufeng Ji; Fazal Ullah; Yanjun Ma; Weibao Kong (Pesticide Biochemistry and Physiology, 2025)

Identifying nitrate pollution of groundwater based on aquifer vulnerability and surface nitrogen loads in the Northern Foot of the Qinling Mountains, China - Yixin Liu; Hui Qian; Yanyan Gao; Siqi Li; Xiaoxin Shi; Zhiming Cao; Qi Long; Yi He; Yandong Ma; Puxia Wu; Yanjun Shen (Journal of Hazardous Materials, 2025)

Mechanism of action of pulsed electric field on lactoferrin: Functional properties, structure and aggregation behavior - Yuhui Ding; Hongfang Cao; Cheng Zhang; Yanjun Tong; Caiyun Wang; Jian He; Wei Zhao; Ruijin Yang (Food Chemistry, 2025)

MOF-based hypocrellin composite nanomaterials as advanced plant-derived photosensitizers for multimodal therapy - Ying'’ao Wu; Yanjun Guo; Kaijie Feng; Miao Li; Hongxue Li; Jiasheng Wu; Pengfei Wang; Rungong Yang; Xiao He; Xiong Yin; Min Li (Chemical Engineering Journal, 2025)

Different responses of soil bacterial necromass carbon and fungal necromass carbon to nitrogen deposition in meadow steppe - Na Jiang; Hao Zhang; Siyu Zhang; Jie Qin; Hui Wang; Yanjun Zhang; Dianlin Yang; Lili Wang; Qiannan Yang; He Ye; Mei Hong; Haifang Zhang (Applied Soil Ecology, 2025)

Desulfurization, desilication, and the separation and recovery of iron from bauxite: A review - Qinglong Fan; Shuai Yuan; Rui Han; Yanjun Li; Jiahao He; Xiaobin Ning (Minerals Engineering, 2025)

Annually laminated stalagmite inferred variations of precipitation and temperature in northern China over the last 150 years - Yingying Wei; Yanjun Cai; Xing Cheng; Gang Xue; Kang’en Zhou; Le Ma; Yanbin Lu; Shouyi Huang; Mei He; Hai Cheng; R. Lawrence Edwards (Climate Dynamics, 2025)

Geniposide Improves Corticosterone-induced Toxicity in PC12 Cells through the NMDARs and BDNF Pathway - Qi Ma; Yu Ma; Shizhuo Sun; Lei Yang; Tian Shi; Boxi Zhang; Bo Shang; Ruiyuan Zhou; Jingyuan Liu; Jiao He; Jing Hu; Yanjun Cao (Cell Biochemistry and Biophysics, 2025)

Antarctic krill oil phosphatidylcholine alleviates visceral hypersensitivity in irritable bowel syndrome: A lipidomics perspective - Siyan Wu; Yanjun Liu; Mengxue He; Zhan Ye; Rui Xu; Yuanfa Liu (Food Bioscience, 2025)

Evaluation of the Association Between Coffee Consumption, Including Type (Instant, Ground), and Addition of Milk or Sweeteners and New-Onset Hypertension and Potential Modifiers - Mengyi Liu; Yanjun Zhang; Ziliang Ye; Sisi Yang; Yuanyuan Zhang; Panpan He; Chun Zhou; Xianhui Qin (Journal of the Academy of Nutrition and Dietetics, 2025)

Enzymatic synthesis of eicosapentaenoyl-lysophosphatidic acid and evaluation of antioxidant and anti-inflammatory properties - Runfeng Du; Yujin Zhang; Yanjun Liu; Mengxue He; Yuanfa Liu (Food Bioscience, 2025)

Engineered hydrogel platform for diabetic wound healing - Jidan Cui; Jianbin Shi; Yanjun Liu; Xianbao Shi; Jin Sun; Zhonggui He; Cong Luo; Shenwu Zhang (Chemical Engineering Journal, 2025)

Passivity-Based Sliding Mode Control for the Robust Trajectory Tracking of Unmanned Surface Vessels Under External Disturbances and Model Uncertainty - Luke Ma; Siyi Pang; Yao He; Yongxin Wu; Yanjun Li; Weijun Zhou (Journal of Marine Science and Engineering, 2025)
This study uses a port-Hamiltonian framework to address trajectory tracking control for unmanned surface vessels (USVs) under unknown disturbances. A passivity-based sliding mode controller is designed, integrating adaptive disturbance estimation and an RBFNN-based uncertainty estimator. Stability is rigorously proven, and simulations confirm superior tracking performance, strong disturbance rejection, and accurate uncertainty estimation.

Extraction of Au(I) from a thiosulfate leach liquor using guanidinium ionic liquid (C8)2dmg+Br− in 20 % (v/v) n-octanol/n-heptane diluent and stripping with aqueous NaCl - Lingli Liu; Guiping Zhu; Chen He; Yanjun Chen; Yewei Qiu; Shixiong Wang; Conghai Zhang; Xiangjun Yang (Hydrometallurgy, 2025)

Zonal gaming and overall enhancement of ecosystem services: A case from the compound area of mine-city and agriculture-forestry-grass in loess region, China - Shufei Wang; Yingui Cao; Shengpeng Li; Xiaoyang Liu; Jinxin He; Yanjun Guan; Zhongke Bai (Ecological Engineering, 2025)

The interactive effect of extreme weather events and PM2.5 on respiratory health among the elderly: a case-crossover study in a high-altitude city - Zhenxu Ning; Yanjun Ma; Shuzhen He; Genshan Li; Ting Xiao; Chunguang Ma; Jing Wu (International Journal of Biometeorology, 2025)

Settlement prediction of a high embankment based on non-linear regression and neural network algorithm - Enhui Yang; Kai Wang; Jinhong He; Kaiwen Liu; Junxin Wang; Haopeng Zhang; Yanjun Qiu (Transportation Geotechnics, 2025)

Numerical study of regular wave dynamics for optimizing coral reef restoration - Jiuming Han; Yanjun Li; Xizeng Zhao; Tao Liu; Yanzhen Gu; Shuangyan He; Peiliang Li; Ruili Sun (Ocean Engineering, 2025)

Electrocatalytic conversion of nitrate to ammonia on the oxygen vacancy engineering of zinc oxide for nitrogen recovery from nitrate-polluted surface water - Wenyang Fu; Yanjun Yin; Shuxian He; Xiangyi Tang; Yinan Liu; Fei Shen; Yan Zou; Guangming Jiang (Environmental Research, 2025)

Balance of heat management and salt-resistance on solar interfacial evaporator actively adjusted by the electric field with periodically changed direction - Shijin Fu; Ziqi He; Yuzhao Ma; Xiuliang Liu; Deqiang He; Yanjun Chen (Desalination, 2024)

3D electric field coupling with Cu foam hydrogel: Achieving efficient and high-speed solar interfacial evaporation - Yanjun Chen; Huiyong Lan; Dongzhi Liu; Xiuliang Liu; Changzheng Li; Deqiang He (Chemical Engineering Journal, 2024)

Sodium humate ameliorates LPS-induced liver injury in mice by inhibiting TLR4/NF-κB and activating NRF2/HO-1 signaling pathways - Weiming Ma; Kexin Liu; Yanjun He; Shouxiang Deng; Yun Liu; Dong Wang (Molecular Biology Reports, 2024)

Differential expression of TOR complex 1 components in Colletotrichum camelliae isolates confers natural resistance to rapamycin - Yuanye Zhu; Yanjun Li; Hong Liu; He Li (Pesticide Biochemistry and Physiology, 2024)

Visible-light-driven photobiocatalytic synthesis of chiral sulfoxides over immobilized chloroperoxidase on magnetic yolk–shell Fe3O4@Cu-H-TiO2 photocatalyst - Xiaoyang Yue; Yuying Hou; Cuiyao Cao; Xue Cao; Haolei Song; Yanjun Jiang; Liya Zhou; Ying He; Xiaobing Zheng; Li Ma; Shijie Li (Journal of Cleaner Production, 2024)

Photocatalytic activation of hydrogen peroxide via a novel CuFe2(PO4)2(OH)2 up-conversion material without rare-earth ions for doxycycline hydrochloride degradation - Yanan Dong; Jing Jiao; Zhihai Liu; Xu He; Panpan Wang; Qinghua Yan; Guocheng Liu; Chengzhi Zhou; Shuaishuai Xin; Yanjun Xin (Chemical Engineering Journal, 2024)

Relationship between environmental evolution and human activities in the northeastern Qinghai-Xizang Plateau throughout the past millennium and its implications for the onset of the Anthropocene - Yang Pu; Xueqiong Wei; Jianbao Liu; Ke Zhang; Beibei Li; Zhudeng Wei; Mengmeng Zhang; Tong He; Yanjun Wang; Xiaohua Shao (Science China Earth Sciences, 2024)
In current research on the Anthropocene, assessing the impact of human activities via stratigraphic records of sediments and demarcating the Anthropocene epoch globally are critical scientific issues that urgently need to be addressed. The northeastern Qinghai-Xizang Plateau (QXP), where humans first settled permanently in large numbers in the QXP, has varying sedimentary environments that are extremely sensitive to human activities. In contrast to other regions of the QXP, the northeastern sector boasts a richer array of climatic and environmental reconstruction sequences. This distinctive feature renders it an exemplary locale for investigating the stratigraphic boundary of the Anthropocene. Through in-depth analysis and integration of existing paleoclimate and paleoenvironment sequences in the northeastern QXP, we draw the following conclusions: (1) Throughout the past millennium, the impact of human activities on the environment of the northeastern QXP has become increasingly significant, especially in the past 200–300 years, gradually overshadowing climatic factors. (2) Since AD 1950, multiple physicochemical indicators related to human activities in the northeastern QXP have shown exponential growth, forming a distinct peak within the past millennium and clearly depicting the global “Great Acceleration” phenomenon and its development process. (3) Intensified human activities have driven swift environmental shifts and “decoupled” the interplay between climatic variations and the ecological environment, propelling the northeastern QXP into the “Early Anthropocene” from the “Late Holocene”. On the basis of the above findings, we construct a model suitable for identifying the stratigraphic boundary of the Anthropocene in the northeastern QXP and note that since the ecological environment in the northeastern QXP has entered the “Early Anthropocene”, the climate signals of certain physicochemical indicators in sediments are gradually becoming weaker, whereas the signals of human activities are becoming stronger.

Study on the source identification and migration and transformation characteristics of heavy metal pollution in sediments of Chaohu Lake Tongyang River Basin - Zhenyu He; Yanjun Li; Bo Kang; Rui Li; Kun Chen; Jie Yang; Yuezan Tao (Environmental Monitoring and Assessment, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

ViTR-Net: An unsupervised lightweight transformer network for cable surface defect detection and adaptive classification - Qi Liu; Deqiang He; Zhenzhen Jin; Jian Miao; Sheng Shan; Yanjun Chen; Mingchao Zhang (Engineering Structures, 2024)

Perspectives on the highly selective oxidation of copper-mediated C3N4-BiVO4 organic-inorganic hybrid catalysts and the efficient generation of reactive oxygen species - Qian Luo; Yue Chen; Yanjun Zhao; Shan He; Shirui Lv; Yuning Ma; Xintong Liu (Chemical Engineering Journal, 2024)

Ratio-fluorescence detection of tert-butylhydroquinone based on non-conjugated polymer dots and gold nanoclusters - Bo Peng; Xueyan He; Chunjuan Wang; Fengxiang Du; Min Zhou; Shengguo Zhao; Yanjun Fang (Food Chemistry, 2024)

Potential mitigation of titanium dioxide nanoparticles against 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis through inhibiting the canonical NF-κB pathway - Yanjun Gao; Langzhi He; Shumin Duan; Hasen Bilige; Lizhi Lyu; Zihui Li; Hongbo Wang; Chen Li; Yun Wang (NanoImpact, 2024)

Mineral transformation, element transport and hydrological impact in weathering at the Bingling Temple Grottoes: Implications for weathering in alkaline environments in NW China - Ruxue Liao; Wenwu Chen; Peiran Liu; Li Wang; Qian Xia; Xiaoyan Yang; Yanjun He; Qinglin Guo (CATENA, 2024)

An integrated study of constraining the initial 230Th of a stalagmite and its implications - Shouyi Huang; Yanjun Cai; Hai Cheng; Gang Xue; Xing Cheng; Mei He; Ruoxin Li; Le Ma; Yingying Wei; Yanbin Lu; Ling Yang; R. Lawrence Edwards (Quaternary Geochronology, 2024)

Investigation of the NH3 consumption and H2O/NO formation during the oxidation of n-heptane and iso-octane blended with ammonia - Dao Zheng; Zhimin Peng; Dong He; Meng Zhang; Jidong Li; Yanjun Ding; Yanjun Du (Fuel, 2024)

Mid-infrared absorption spectroscopy measurements and model improvements during the oxidation of ammonia/ethanol and ammonia/diethyl ether blends in a shock tube - Dao Zheng; Dong He; Yanjun Du; Meng Zhang; Jidong Li; Yanjun Ding; Zhimin Peng (Fuel, 2024)

Biocatalytic membranes with crosslinked enzyme aggregates for micropollutant removal - Guanhua Liu; Luting Wang; Anan Zhao; Leijie Guo; Liya Zhou; Ying He; Li Ma; Yunting Liu; Jing Gao; Yanjun Jiang (Chemical Engineering Journal, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Historical trends and pollution assessment of heavy metals in core sediments from the Jiangsu offshore area, China - Li He; Shenghui Jiang; Xuhui Chen; Haiyan Cheng; Peng Ye; Lu Chen; Yuan Liu; Yanjun Yin; Xing Leng (Regional Studies in Marine Science, 2023)

Effects of gamma irradiation on the nutritional quality and physicochemical properties of Morchella angusticeps - Ailian Meng; Peng Gao; Pan Xu; Xin Jia; Jiang He; Yan Wang; Qian Chen; Yanjun Zhang; Yalu Qiu; Min Huang; Hao Chen (Food Bioscience, 2023)

Positive association between ambient air pollutants and incident kidney stones - Xiaoqin Gan; Yanjun Zhang; Panpan He; Ziliang Ye; Chun Zhou; Mengyi Liu; Sisi Yang; Yuanyuan Zhang; Xianhui Qin (Environmental Science and Pollution Research, 2023)

A dual-enzyme microreactor based on encapsulation and covalent bond for enzymatic electrocatalytic CO2 reduction - Guanhua Liu; Lirong Wang; Lihang Yan; Hao Zhao; Yaoxuan Li; Liya Zhou; Ying He; Li Ma; Yunting Liu; Jing Gao; Yanjun Jiang (Chemical Engineering Journal, 2023)

Removal of tar from waste textiles by molten carbonates pyrolysis in bubbling reactor - Yaohong He; Yanjun Hou; Cheng Wang; Shan Wang; Yi Wei (Fuel, 2023)

Evolution of the foreland basins on either side of the Tian Shan and implications for lithospheric architecture - Chao Li; Shengli Wang; Yanjun Wang; Zhiyuan He; Chuang Sun; Hugh Sinclair; Yan Chen; Shaowen Liu; Guohui Chen; Fei Xue (Marine and Petroleum Geology, 2023)

Study on detection method of microplastics in farmland soil based on hyperspectral imaging technology - Lijia Xu; Yanjun Chen; Ao Feng; Xiaoshi Shi; Yanqi Feng; Yuping Yang; Yuchao Wang; Zhijun Wu; Zhiyong Zou; Wei Ma; Yong He; Ning Yang; et al. (Environmental Research, 2023)

Mapping foliar photosynthetic capacity in sub-tropical and tropical forests with UAS-based imaging spectroscopy: Scaling from leaf to canopy - Shuwen Liu; Zhengbing Yan; Zhihui Wang; Shawn Serbin; Marco Visser; Yuan Zeng; Youngryel Ryu; Yanjun Su; Zhengfei Guo; Guangqin Song; Qianhan Wu; He Zhang; et al. (Remote Sensing of Environment, 2023)

Applying mass flow analysis and aeration optimization strategy to reduce energy consumption of a full-scale anaerobic/anoxic/oxic system - Lu-Man Jiang; Wen Zhang; Yunhui Li; Yanjun Shao; Zhenjian Zhang; Ming Zhang; Junli He; Ji Qiu; Wenxiang Li; Junwei Wang; Zhen Zhou (Journal of Water Process Engineering, 2023)

Conversion and syngas production of toluene as a biomass tar model compound in chemical looping reforming - Ming Luo; Ruicong Shen; Yanjun Qin; Honglin Liu; Yiran He; Qingrui Wang; Junfeng Wang (Fuel, 2023)

Enlarged fins of Tibetan catfish provide new evidence of adaptation to high plateau - Liandong Yang; Ning Sun; Honghui Zeng; Ying Wang; Wenjun Chen; Zufa Ding; Yang Liu; Jing Wang; Minghui Meng; Yanjun Shen; Jingliang Kang; Xiuhui Ma; et al. (Science China Life Sciences, 2023)

Comparative study of sediment phosphorus immobilization via the addition of lanthanum-modified and thermal-modified drinking water treatment sludge - Fei Sun; Yu Chen; Liwenze He; Jingxiang Tang; Yanjun Li (Environmental Science and Pollution Research, 2023)

A smartphone-assisted ratiometric colorimetric and fluorescent probe for triple-mode determination of nitrite based on MnO2 nanoparticles and carbon quantum dots - Bo Peng; Chunjuan Wang; Xueyan He; Yongjun Ma; Min Zhou; Xin Ma; Shengguo Zhao; Yanjun Fang (Food Chemistry, 2023)

The Potential of NLRP3 Inflammasome as a Therapeutic Target in Neurological Diseases - Wenfang He; Zhiping Hu; Yanjun Zhong; Chenfang Wu; Jinxiu Li (Molecular Neurobiology, 2023)

Rapid determination and health risk assessment of neonicotinoids in source water and tap water of the tropical Hainan Island, China - Zengheng Xiong; Yan Wu; Yang Zhou; Shuhai He; Danyu Huang; Mingshan Zhang; Yanjun Jiang; Long Cheng; Zhendong Zhao; Hongwei Zhao; Huan Lin (Environmental Science and Pollution Research, 2023)

Relations of residential green and blue spaces with new-onset chronic kidney disease - Mengyi Liu; Ziliang Ye; Panpan He; Sisi Yang; Yanjun Zhang; Chun Zhou; Yuanyuan Zhang; Xiaoqin Gan; Xianhui Qin (Science of The Total Environment, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

Determination of rock quality designation (RQD) using a novel geophysical approach: a case study - Muhammad Hasan; Yanjun Shang; Xuetao Yi; Peng Shao; He Meng (Bulletin of Engineering Geology and the Environment, 2023)

Critical tectonic events and their geological controls on deep buried coalbed methane accumulation in Daning-Jixian Block, eastern Ordos Basin - Taotao Yan; Shan He; Shuai Zheng; Yadong Bai; Wei Chen; Yanjun Meng; Shangwen Jin; Huifang Yao; Xiaobao Jia (Frontiers of Earth Science, 2023)

Advancing the bioconversion process of food waste into methane: A systematic review - Endashaw Workie; Vinor Kumar; Amit Bhatnagar; Yiliang He; Yanjun Dai; Yen Wah Tong; Yinghong Peng; Jingxin Zhang; Cunbin Fu (Waste Management, 2023)

Applications of Computed Tomography (CT) in environmental soil and plant sciences - Huan Zhang; Hailong He; Yanjun Gao; Ahmed Mady; Vilim Filipović; Miles Dyck; Jialong Lv; Yang Liu (Soil and Tillage Research, 2023)

Review on recent progress in on-line monitoring technology for atmospheric pollution source emissions in China - Huanqin Wang; Jitong Zhou; Xue Li; Qiang Ling; Hongyuan Wei; Lei Gao; Ying He; Ming Zhu; Xiao Xiao; Youjiang Liu; Shan Li; Chilai Chen; et al. (Journal of Environmental Sciences, 2023)

Mixed heavy metals exposure affects the renal function mediated by 8-OHG: A cross-sectional study in rural residents of China - Xiaoyu Tian; Xiaobing Shan; Li Ma; Chenyang Zhang; Mei Wang; Jie Zheng; Ruoyi Lei; Li He; Jun Yan; Xun Li; Yanjun Bai; Keqin Hu; et al. (Environmental Pollution, 2023)

Hollowing of nanoparticle membrane by sacrificing phase-inversion-formed nanohydrogel to enhance solar–steam generation efficiency - Yu Ma; Xiaoli Zhao; Yanjun Shen; Yi Wang; Bin He (Desalination, 2023)

High performance Na3V2(PO4)3 with nitrogen-chlorine co-doped carbon matrix in-situ synthesized in chitosan quaternary ammonium hydrogel for sodium ion batteries - Jiahao Li; Yanjun Chen; Shengnan He; Yaxiong Yang; Yanzhong Wang; Li Guo (Chemical Engineering Journal, 2023)

Unravelling the regulation mechanism of nanoflower shaped Na3V2(PO4)3 in methanol–water system for high performance sodium ion batteries - Shiqi Sun; Yanjun Chen; Qiang Bai; Zhen Tian; Que Huang; Changcheng Liu; Shengnan He; Yaxiong Yang; Yanzhong Wang; Li Guo (Chemical Engineering Journal, 2023)

The Critical Factors and Preventive Measures of Impoundment of Tailings Using Active Surface Subsidence Zones - Yang Liu; Yanjun Zhou; Rongxing He; Jianli Cao; Fengyu Ren; Fu Yu; Lu Yue (Geotechnical and Geological Engineering, 2023)

In vitro and in vivo efficacy of cefiderocol plus tigecycline, colistin, or meropenem against carbapenem-resistant Acinetobacter baumannii - Wentao Ni; Yifan Wang; Xinqian Ma; Yukun He; Jin Zhao; Jie Guan; Yanjun Li; Zhancheng Gao (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Flotation de-inking for recycling paper: contrasting the effects of three mineral oil-free offset printing inks on its efficiency - Shujie Yang; Jianbin Shen; Tiefei He; Chao Chen; Junming Wang; Yanjun Tang (Environmental Science and Pollution Research, 2022)

Temporal genetic variation of the Chinese longsnout catfish (Leiocassis longirostris) in the upper Yangtze River with resource decline - Yanjun Jin; Kun He; Peng Xiang; Xiaodong Wang; Lintian Tong; Zhen Wei; Xiuyue Zhang; Zhaobin Song (Environmental Biology of Fishes, 2022)

Evaluation of Engineering Rock Mass Quality via Integration Between Geophysical and Rock Mechanical Parameters - Muhammad Hasan; Yanjun Shang; Peng Shao; Xuetao Yi; He Meng (Rock Mechanics and Rock Engineering, 2022)

Stimulation of melanin synthesis by UVB is mediated by NO/cGMP/PKG cascade targeting PAK4 in vitro - Linli Xue; Lucheng Chang; Yilei Li; Yanjun Dong; Xiaoyan He (In Vitro Cellular & Developmental Biology - Animal, 2021)

Variations of soil organic matters and plant cuticular waxes along an altitude gradient in Qinghai-Tibet Plateau - Luhua Yao; Na Guo; Yuji He; Yu Xiao; Yang Li; Jianhua Gao; Yanjun Guo (Plant and Soil, 2021)

Population genetic divergence in Lycium chinense Mill. (Solanaceae) is driven by both hybridization and geo-environmental factors - Lulu Yang; Yan He; Shuhui Wang; Yanjun Zhang; Ying Wang; Qiong Liang (Genetic Resources and Crop Evolution, 2020)

Present-day Tectonic Stress Field and GPS Observations in Hubei Province, Central China - Yanjun Dong; Fanxi Liao; Dongzhen Wang; Chengchen Du; Kai He (Pure and Applied Geophysics, 2020)

Faba Bean Organs Differed in Their Effects on Maize Seed Germination Rate and Soil Microbial Activities as well as Their Decomposition Patterns in a Regosol Soil - Zhibin He; Luhua Yao; Xuefeng Zhang; Yang Li; Dengke Wang; Lin Kang; Cui Cui; Aiying Huang; Ruiji Yang; Qianlin Xiao; Yanjun Guo (Journal of Soil Science and Plant Nutrition, 2020)

A transcriptomic analysis of Nsmce1 overexpression in mouse hippocampal neuronal cell by RNA sequencing - Mengting Gong; Zhen Wang; Yanjun Liu; Wenxing Li; Shoudong Ye; Jie Zhu; Hui Zhang; Jing Wang; Kan He (Functional & Integrative Genomics, 2020)

Genome-wide identification of long non-coding RNAs and circular RNAs reveal their ceRNA networks in response to cucumber green mottle mosaic virus infection in watermelon - Yuyan Sun; Huiqing Zhang; Min Fan; Yanjun He; Pingan Guo (Archives of Virology, 2020)

Growing‐season temperature and precipitation are independent drivers of global variation in xylem hydraulic conductivity - Pengcheng He; Sean M. Gleason; Ian J. Wright; Ensheng Weng; Hui Liu; Shidan Zhu; Mingzhen Lu; Qi Luo; Ronghua Li; Guilin Wu; Enrong Yan; Yanjun Song; et al. (Global Change Biology, 2020)
Stem xylem‐specific hydraulic conductivity ( K S ) represents the potential for plant water transport normalized by xylem cross section, length, and driving force. Variation in K S has implications for plant transpiration and photosynthesis, growth and survival, and also the geographic distribution of species. Clarifying the global‐scale patterns of K S and its major drivers is needed to achieve a better understanding of how plants adapt to different environmental conditions, particularly under climate change scenarios. Here, we compiled a xylem hydraulics dataset with 1,186 species‐at‐site combinations (975 woody species representing 146 families, from 199 sites worldwide), and investigated how K S varied with climatic variables, plant functional types, and biomes. Growing‐season temperature and growing‐season precipitation drove global variation in K S independently. Both the mean and the variation in K S were highest in the warm and wet tropical regions, and lower in cold and dry regions, such as tundra and desert biomes. Our results suggest that future warming and redistribution of seasonal precipitation may have a significant impact on species functional diversity, and is likely to be particularly important in regions becoming warmer or drier, such as high latitudes. This highlights an important role for K S in predicting shifts in community composition in the face of climate change.

Effects of the configuration of a baffle–avalanche wall system on rock avalanches in Tibet Zhangmu: discrete element analysis - YuZhang Bi; SiMing He; YanJun Du; XinPo Sun; XinPo Li (Bulletin of Engineering Geology and the Environment, 2019)

An engineering site suitability index (ESSI) for the evaluation of geological situations based on a multi-factor interaction matrix - Kun Li; Yanjun Shang; Wantong He; Daming Lin; Muhammad Hasan; Kaiyang Wang (Bulletin of Engineering Geology and the Environment, 2019)

Numerical analysis of effect of baffle configuration on impact force exerted from rock avalanches - YuZhang Bi; YanJun Du; SiMing He; XinPo Sun; DongPo Wang; XinPo Li; Heng Liang; Yong Wu (Landslides, 2018)

Modification of rock mass strength assessment methods and their application in geotechnical engineering - Daming Lin; Kaiyang Wang; Kun Li; Wantong He; Weixing Bao; Renmao Yuan; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2017)

Transcription factor Sp1 is necessary and functional in regulating expression of oncogene ZNF703 - Xiaolin Liao; Yongjie Lu; Junbao Yang; Tao Kuang; Lilin Jiang; Yanjun Wang; Huiqun Kang; Bo Jiang; Xiaoli Zhou; Sheng He (Genes & Genomics, 2017)

HOTAIR functions as a competing endogenous RNA to regulate PTEN expression by inhibiting miR-19 in cardiac hypertrophy - Yanjun Lai; Shuai He; Liming Ma; Hong Lin; Biyun Ren; Jing Ma; Xinyu Zhu; Shifang Zhuang (Molecular and Cellular Biochemistry, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Two new coumarins from the bark of Streblus indicus (Bur.) Corner - Ruijie He; Shengping Deng; Hui Nie; Yan Huang; Buming Liu; Ruiyun Yang; Shuai Huang; Dexiong Zhou; Huangcan Chen; Jun Li; Yanjun Zhang (Natural Product Research, 2017)

Deformation and failure of a tunnel in the restraining bend of a strike–slip fault zone: an example from Hengshan Mountain, Shanxi Province, China - Daming Lin; Renmao Yuan; Yanjun Shang; Weixing Bao; Kaiyang Wang; Zhongjian Zhang; Kun Li; Wantong He (Bulletin of Engineering Geology and the Environment, 2017)

Comparison of winter wheat yield sensitivity to climate variables under irrigated and rain-fed conditions - Dengpan Xiao; Yanjun Shen; He Zhang; Juana P. Moiwo; Yongqing Qi; Rende Wang; Hongwei Pei; Yucui Zhang; Huitao Shen (Frontiers of Earth Science, 2016)

Effects of a Cardiotonic Medicine, Danshen Pills, on Cognitive Ability and Expression of PSD-95 in a Vascular Dementia Rat Model - Yanzhen Zhu; Yanjun Zeng; Caigu He; Shu Jiang; Linying Zhou; Yumei Huang; Changhui Qiang; Yiyan Jiang (Neurophysiology, 2016)

Impact of warming climate and cultivar change on maize phenology in the last three decades in North China Plain - Dengpan Xiao; Yongqing Qi; Yanjun Shen; Fulu Tao; Juana P. Moiwo; Jianfeng Liu; Rede Wang; He Zhang; Fengshan Liu (Theoretical and Applied Climatology, 2016)

Spatiotemporal variability of winter wheat phenology in response to weather and climate variability in China - Dengpan Xiao; Juana P. Moiwo; Fulu Tao; Yonghui Yang; Yanjun Shen; Quanhong Xu; Jianfeng Liu; He Zhang; Fengshan Liu (Mitigation and Adaptation Strategies for Global Change, 2015)

Modifications to the GSI for granite in drilling - Daming Lin; Yan Sun; Wei Zhang; Renmao Yuan; Wantong He; Bo Wang; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2014)

Synthesis of α-Fe2O3 nanofibers for applications in removal and recovery of Cr(VI) from wastewater - Tongyan Ren; Ping He; Weiling Niu; Yanjun Wu; Lunhong Ai; Xinglong Gou (Environmental Science and Pollution Research, 2013)

Regeneration of insulin monomers from amyloid fibrils by a NH3/H2O2 two-step method - Rui Liu; Rongxin Su; Yanjun Yu; Wei Qi; Libing Wang; Zhimin He (Biotechnology Letters, 2012)

Genome-wide analysis of Aux/IAA gene family in Solanaceae species using tomato as a model - Jian Wu; Zhen Peng; Songyu Liu; Yanjun He; Lin Cheng; Fuling Kong; Jie Wang; Gang Lu (Molecular Genetics and Genomics, 2012)

Wheat vacuolar H+-ATPase subunit B cloning and its involvement in salt tolerance - Li Wang; Xiaoliang He; Yanjun Zhao; Yinzhu Shen; Zhanjing Huang (Planta, 2011)

Prediction of permafrost changes in Northeastern China under a changing climate - Zhi Wei; HuiJun Jin; JianMing Zhang; ShaoPeng Yu; XuJun Han; YanJun Ji; RuiXia He; XiaoLi Chang (Science China Earth Sciences, 2011)

Nitric oxide enhances melanogenesis of alpaca skin melanocytes in vitro by activating the MITF phosphorylation - Yanjun Dong; Haidong Wang; Jing Cao; Jie Ren; Ruiwen Fan; Xiaoyan He; George W. Smith; Changsheng Dong (Molecular and Cellular Biochemistry, 2011)

Comparative QSAR modeling of antitumor activity of ARC-111 analogues using stepwise MLR, PLS, and ANN techniques - Yanjun Yu; Rongxin Su; Libing Wang; Wei Qi; Zhimin He (Medicinal Chemistry Research, 2010)

Electrophysiological and Behavioral Responses of Ips subelongatus to Semiochemicals from Its Hosts, Non-hosts, and Conspecifics in China - Qing-He Zhang; Fredrik Schlyter; Guofa Chen; Yanjun Wang (Journal of Chemical Ecology, 2007)

Study of 1998 heavy rainfall over the Yangtze River Basin using TRMM data - Cheng Minghu; He Huizhong; Mao Dongyan; Qi Yanjun; Cui Zhehu; Zhou Fengxian (Advances in Atmospheric Sciences, 2001)